Academic Integrity and Internationalization: the Proceedings of Annual Conference - (:unkn) unknown (KAZGUU University, Nazarbayev University, 2018)
The Proceedings of Annual Conference on Academic Integrity is peer reviewed proceedings of the Annual Conference on Academic Integrity organized by the Higher School of Economics of KAZGUU University and Nazarbayev University in Astana, Kazakhstan. Established in 2015, the Conference brings together established scholars, early career researchers, practitioners and graduate students from national and international Universities and institutions. The aim of the conference is to share theoretical and empirical research on academic integrity; to debate best practices from around the world and to conceptualize new approaches. The focus of the 3rd Annual Conference is Academic Integrity and Internationalization. Many important challenges arise from this dynamic context: sustaining shared values and practices of academic integrity across borders; ensuring continuity of high quality standards in transnational education; and using technologies to promote academic integrity (whilst avoiding abuse of technologies by students to breach rules of integrity) are some of them.
Keywords: KAZGUU University; Nazarbayev University; Academic Integrity